Community empowerment in Latin American sex workercommunities: a systematic review - Vargas Rodríguez, Diana Milena; Martínez Santis, Tatiana; Vargas Rodríguez, Diana Milena; Martínez Santis, Tatiana; Vargas Rodríguez, Diana Milena; Martínez Santis, Tatiana (Corporación Universitaria Americana, 2023)
Introduction: The research was intended to conduct an analysis of the notion of community empowerment and how it is used in sex worker collectives, was conducted through an exploration of academic publications from Latin American nations over the last decade. Objective: To critically analyze the notion of community empowerment and its relevance to sex worker collectivities by exploring studies conducted in Latin America (Latam) over the last decade. Methodology: For the study, a systematic review of the available literature was developed through a Research Analysis Matrix (RAI) to examine the notion of community empowerment and its relationship with sex workers in Latam, in coherence with a conceptual theoretical framework that has Community Psychology and gender studies as its central axis, the applicability of community empowerment resulting from the intersectionality of sex workers in Latin American contexts is discussed. Conclusion: Sex work was understood as a concept of resignification, which has given rise to vindicating visions translated into an exercise of female empowerment by allowing them access to resources that can help their transformation at the individual, community and social levels.